Meet Samantha: An American Girl - Adler, Susan S (Pleasant Company Publications Incorporated, 1986)
Nine-year-old Samantha and her servant friend Nellie have a midnight adventure when they try to find out what has happened to the seamstress who has suddenly left her job
Keywords: Social Issues; Friendship; Juvenile Fiction